Political, Social Exchange in The Selection of Concurrent Regional Heads in Indonesia - Suryadi, Budi; Ahmad, Bachruddin Ali (International Journal of Psychosocial Rehabilitation, 2020)
The selection of regional heads in Indonesia had already begun in 2005 until now has been implemented for about fifteen years. Then in the year 2015 changed the pattern of application to the selection of regional heads simultaneously. The research method uses a qualitative approach with phenomenological variants and interactive data model analysis with data collection flows, data reduction, data presentation and withdrawal conclusions. The results of the study showed that the regional head of concurrent elections in Indonesia tended to political social exchange in local communities. This social, political exchange as a development of the old habits of the local community in his social life, where social exchange is experiencing a standing in the political election of regional heads simultaneously. Political, social exchange in the form of goods and money, which is received as a form of exchange of decision in the vote of regional head. This social exchange is due to factors shifting the value of the local community, not institutionalized the prohibition of political money in local communities and the absence of the transparency of local community leaders.